A REVIEW ON THE INVASIVE ALIEN SPECIES, Thrips parvispinus (KARNY) – BIOECOLOGY, HOST RANGE AND MANAGEMENT - JEYASHREE J; ARIVUDAINAMBI S (The Bioscan, 2024)
Invasive alien species (IAS) are among the leading drivers of biodiversity loss, severely impacting agricultural ecosystems. Thrips parvispinus (Karny), commonly known as the Tobacco black thrips, has emerged as a major pest, affecting a wide range of agricultural and horticultural crops globally. Native to Southeast Asia, T. parvispinus has rapidly expanded its distribution due to globalization, climate change, and international trade. This pest is characterized by its high reproductive rate, adaptability to diverse environmental conditions, and ability to displace native thrips species, resulting in extensive crop damage. T. parvispinus has been recorded in various regions, including Southeast Asia, Australia, Greece, and multiple Indian states, where it has significantly impacted chilli, papaya, and other economically important crops. The species undergoes a complex life cycle, with five immature stages, and exhibits a strong preference for flowers and leaves, causing severe plant damage. Population dynamics are influenced by factors such as host plant abundance, temperature, and light intensity. Moreover, T. parvispinus has been identified as a vector of plant viruses, further exacerbating its impact on agricultural production. This review consolidates existing knowledge on the bioecology, global distribution, host range, and population dynamics of T. parvispinus. It also explores sustainable management strategies to mitigate its effects on agriculture. Understanding its invasiveness is crucial for developing integrated pest management approaches to minimize economic losses and ensure sustainable crop production.